Agrobacterium mediated manipulation of the expression of an polysaccharide biosynthetic phosphoglucose isomerase gene to improve polysaccharide production in Sanghuangporus vaninii - Zihao Li; Weihang Li; Yi Zhou; Congtao Xu; Jinlong Pan; Yajie Zou (Food Chemistry: Molecular Sciences)
The Sanghuangporus vaninii polysaccharide plays diverse biological roles in enhancing human health; nonetheless, the fundamental process of polysaccharide synthesis in S. vaninii remains unclear. Phosphoglucose isomerase (PGI) is a key enzyme in polysaccharide synthesis, which can affect the energy metabolism and polysaccharide synthesis of organisms. To elucidate the potential role of PGI in S. vaninii polysaccharide metabolism, the interference transformation system of SvPgi was constructed to study the related functions. It was found that the interference with the expression of SvPgi could increase the polysaccharide content of mycelium by 31.24 % and 41.28 %, and the extracellular polysaccharide content by 83.57 % and 91.83 %, respectively. In addition, regulation of SvPgi expression resulted in significant changes in polysaccharide metabolic pathway, monosaccharide composition and cell wall component content, suggesting that SvPgi could be an ideal molecular target for engineering high-yielding polysaccharide strains. Our findings reveal that SvPgi acts as a critical metabolic switch balancing mycelial growth and polysaccharide biosynthesis in S. vaninii. While RNAi-mediated silencing of SvPgi significantly enhances polysaccharide yields, the concomitant biomass reduction underscores the need for refined regulatory approaches to decouple growth from biosynthesis. This mechanistic insight paves the way for future strain engineering targeting PGI activity under controlled conditions.